The EFFECT OF SUBLETHAL CONCENTRATION OF LEAD ON DELTA-AMINOLEVULINIC ACID DEHYDRATASE ACTIVITY AND HEMATOLOGICAL PARAMETERS IN THE JAVANESE CARP Puntius gonionotus (BLEEKER) - Patimah I (Research Center for Fisheries, 1997)
The activity of the erythrocyte delta-Aminolevulinie acid dehydratase (ALA-D) of carp, Puntius gonionotus, was measured under a variety of lead (Pb) exposure conditions.